Political Ethnobiology - Soldati, Gustavo Taboada; Almada, Emmanuel Duarte (Ethnobiology and Conservation, 2024)
Indigenous peoples and local communities continue to suffer various violations and ethnocide. Their knowledge systems and biodiversity management practices, which are fundamental to overcoming the central crises of today, are under threat. Consolidating a political approach in Ethnobiology can contribute to the struggles and rights of Indigenous Peoples and Local Communities. Therefore, we present (i) a brief history of the political approach in Ethnobiology, (ii) conceptual and theoretical contributions to an anti-oppressive Ethnobiology, (iii) a proposal for a conceptual and programmatic synthesis for Political Ethnobiology, and (iv) examples of investigations and concrete actions in the field of Political Ethnobiology.